The impact of the labor deficit on the development of the agricultural sector of the Republic of Moldova - Viorel Tureţchi; Tatiana Tureţchi (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The problem of providing the national agricultural sector with labor force has increased with the intensification of the process of migration of the rural population to cities or abroad. As a result, this exodus considerably decreased the supply of labor in the given sector, creating a constant deficit of the given resource. The purpose of the given work is to reflect the considerations of the emergence and evolution of the given subject, the analysis of the current situation and in perspective, the definition of the means of improving the capacity of labor insurance of the agricultural sector. The general research methods (empirical and theoretical methods) were used in the preparation of the report, the analysis of statistical data reflecting the demographic changes in the rural area as well as the dynamics of the involvement of the rural population in the agricultural production process were widely applied. The report reflects both the analysis of statistical data and the derived conclusions, and the results are interpreted through the prism of social changes and economic reforms carried out in the rural area of the Republic of Moldova.
Keywords: R23; Q15; Q18; 330; agriculture; workforce; reforms; crisis; impact